A Critical Review of School-Based Nutrition Education Contents: Strengths, Gaps and Ways Forward (Interdisciplinary Research in Education, 2024)
Nutrition education (NE) plays a crucial role in shaping the health and well-being of schoolchildren. This paper critically examines NE contents in school education as outlined in the National Curriculum Framework (NCF)-2019, focusing on its strengths, gaps, and potential ways forward. The paper is developed reviewing literature, particularly government documents, published articles, and dissertations. The findings reveal that the NCF focuses on the basics of food and nutrition, healthy eating behaviors, locally available foods, balanced diet, essential nutrients, food adulteration, malnutrition, and the effects of junk food. Additionally, the curriculum addresses issues like food adulteration, food security, and consumer rights and partially aligns with the strategic objectives and programs of the Multi-Sector Nutrition Plan (MSNP). However, the integration of global perspectives like Sustainable Development Goals (SDGs), climate change, and sustainable agriculture are limited to integrate into the curriculum. The study recommends addressing these gaps by incorporating global perspectives on topics such as climate change, sustainable agriculture, the SDGs, and the MSNP targets.